Plant remains from the Linear Pottery Culture settlement at sites Modlniczka 3 and 4, Kraków district. New sources for understanding agriculture in the Early Neolithic in southern Poland. - Magda Dagmara Kapcia; Maciej Nowak (Acta Palaeobotanica)
The aim of the archaeobotanical research of plant macro remains assemblage from the Early Neolithic settlement at Modlniczka in southern Poland is to study plants (fruit and seeds), cultivated and wild species used by the oldest farming groups during the early phase of occupation at the sites. The results were obtained from 62 samples from two archaeological sites, Modlniczka sites 3 and 4, likely forming one large settlement. Only charred plant remains were taken into account. Among cultivated plants, two species of hulled wheat, Triticum dicoccon and Triticum monococcum , and common barley Hordeum vulgare were documented. Among wild plants, several taxa were found, including Chenopodium t. album , Ch. polyspermum , Fallopia convolvulus , Bromus sp. Numerous seeds of Chenopodium t. album indicates that this plant could have been used as part of a diet. In addition, hazelnut ( Corylus avellana ) shells were found.